BY MEANS OF LINDEBERG’S CENTRAL LIMIT THEOREM - SOMAYASA, WAYAN (Jurnal Matematika; Vol 1 No 1 (2010)DO - 10.24843/JMAT.2010.v01.i01.p11)
We study the construction of a version of standard Brownian sheet called h -generalized standard Brownian sheet. It is shown by means of Lindeberg’s theorem that it is a limit process of a sequence of partial sums processes of independent random variables in the sense of weak convergence in the metric space of continuous functions on the compact region [0,1]×[0,1]. Based on this convergence we approximate by simulation the quantiles of Kolmogorov, Kolmogorov-Smirnov and Cramér-von Mises type statistics which are defined as continuous functionals of the process.
Keywords: h -generalized standard Brownian sheet, weak convergence, model-check, tightness.